Anatomical and Radiological Assessments of Injectate Spread Stratified by the Volume of the Pericapsular Nerve Group Block. (17th February 2023) - Kim, Ji Yeong; Kim, Jiyoung; Kim, Do-Hyeong; Han, Dong Woo; Kim, Sang Hyun; Kim, Donghyun; Chung, Siwook; Yu, Sanghyuck; Lee, U-Young; Park, Hue Jung
Abstract : BACKGROUND: The pericapsular nerve group (PENG) block was recently suggested as a regional technique for managing acute pain after hip surgery. However, few anatomical studies have confirmed the spread of injectate during the PENG block. This cadaver study aimed to analyze injectate spread to the target nerves during single-injection ultrasound-guided PENG block. METHODS: Ultrasound-guided PENG block with 3 different injectate volumes (10, 20, or 30 mL) was performed in 18 cadavers. Injectate spread by the volume was first evaluated on computed tomography, followed by cadaver dissection. The spread of the dye over the pelvis and lower limb was evaluated. RESULTS: The articular branches of the femoral nerve were stained nearly sufficiently with 20- and 30-mL specimens. The femoral nerve itself was stained simultaneously in six of 12 (50%) 20-mL specimens and 12 of 12 (100%) 30-mL specimens. The accessory obturator nerve was observed only in three (9%) of 36 specimens. The articular branches of the obturator nerve were rarely affected, regardless of injectate volume (1/12, 10 mL specimens; 2/12, 20 mL specimens; 1/12, 30 mL specimens; P > .999). Rather, the obturator nerve was affected. However, the obturator nerve was not stained consistently even with 30 mL of injectate (50%). CONCLUSIONS: After combining the dissection and radiological findings, the single-injection ultrasound-guided PENG blocks with volumes of 10, 20, and 30 mL do not support motor sparing or selective anterior hip capsule innervation in a clinical setting. If early rehabilitation is needed, high-volume PENG block might not be the ideal option, and persisting pain after PENG block might be attributed in part to the lack of obturator nerve articular branches blockade.